Perspektif Islamphobia Pasca Tragedi 11 September 2001 - Maisi Rafidah (Medan Resource Center, 2021)
This paper is compiled using a qualitative data collection method which is based on a literature review, whether in the form of journals or books. And aims to study Islamophobia, Terrorism and Sharia. The collapse of the WTC building and the destruction of the pentagon building on Tuesday 11 September 2001 in New York Washington resulted in Muslims experiencing discrimination from non-Muslim Americans. The collapse of the WTC building and the destruction of the Pentagon Building on September 11, 2001, resulted in a world conflict involving the United States government and Islam. The increase in terror acts that have occurred in various countries has had many negative impacts on the development and development of a country as well as positive impacts on Muslims and Muslims in the United States. Not only that, American Muslims also do not practice some Shari'a because of the laws that deal with the sphere of government and the state. Even Sharia emphasizes that the rule of law in a society must be carried out by the state.